Novel anti-stripping TNTs dental implant prepared with assistance of laser

Laser-assisted preparation of L-TNTs array films with graded micro-patterned structures solves the problem of easy peeling of TNTs under mechanical stress, significantly improves anti-peeling and wear resistance, promotes osteogenesis function, and improves dental implants biocompatibility and clinical application.

CN119235483APending Publication Date: 2025-01-03STOMATOLOGICAL HOSPITAL AFFILIATED TO WENZHOU MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411360432.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The TNTs coatings in existing titanium and titanium alloy dental implants are prone to cracking, stratification and peeling under mechanical stress, resulting in poor biological function, especially in patients with osteoporosis and diabetes, and now Enhancement measures cannot effectively prevent wear and fall off.

Method used

Laser-assisted preparation of L-TNTs array films with interlocking protrusions and depression patterns, forming microline patterns on the surface of titanium-based materials through picosecond laser etching technology, and anodizing them in these areas to avoid The direct contact between the nanotubes and the bone interface enhances anti-stripping and wear resistance.

Benefits of technology

Significantly improve the anti-stripping and wear resistance of L-TNTs, maintain the integrity of nanotube structure, promote the growth and differentiation of osteoblasts, extend the service life of the implant, and improve the intraocular diseases in osteoporosis and diabetes. Repair effects in patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119235483A_ABST
    Figure CN119235483A_ABST
Patent Text Reader

Abstract

The invention relates to the field of titanium and titanium alloy processing, in particular to a laser-assisted prepared novel anti-stripping TNTs dental implant, and a preparation method of a novel anti-stripping L-TNTs array film comprises the following steps: (1) spin-coating photoresist on a non-pattern area on the surface of a titanium-based material; (2) etching a pattern area on the surface of the titanium-based material; (3) carrying out anodic oxidation on the etched region; and (4) removing the photoresist to obtain the novel anti-stripping TNTs array film prepared by laser assistance. The surface structure of the novel anti-stripping L-TNTs array film is that TNTs are embedded in a groove formed by etching. According to the novel anti-stripping L-TNTs array film disclosed by the invention, the anti-stripping and wear-resisting properties of the L-TNTs are enhanced through accurate control of the size of the micro-pattern structure of the novel anti-stripping L-TNTs array film; the L-TNTs can also be prepared on the bent surface of the titanium implant, and the capability of promoting osteoblast growth and differentiation of the nanotube structure is still reserved; the L-TNTs improve the performance of the whole implant and promote the commercial application of the TNTs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of titanium and titanium alloy processing, and in particular to a new type of anti-stripping TNTs dental implant prepared with the aid of laser. Background Art

[0002] Titanium (Ti) and its alloys are widely recognized as the materials of choice for dental implants in clinical applications due to their excellent biocompatibility and mechanical properties. However, their biological functions are not yet fully understood, and their restorative effects are still unsatisfactory for patients with diseases such as osteoporosis and diabetes. Studies have shown that titanium dioxide nanotube (TNTs) coatings formed on the titanium surface by anodization have multiple biological functions and significantly enhance the bone bonding ability of titanium implants. The vertically arranged TNTs first serve as a platform for local drug delivery, facilitating the controlled release of drug molecules. In addition, the increased surface area of ​​TNTs enhances their ability to resist bacterial infection and oxidative stress. Moreover, the elastic modulus of the hollow tubular structure of TNTs is similar to that of cancellous bone, which can cleverly manage load distribution and energy dissipation, reduce stress shielding effects, and thus extend the service life of implants. Despite these advantages, TNTs are prone to cracking, delamination, and peeling under mechanical stress. When implanted into the bone, TNTs encounter friction, and after being embedded in the jawbone, they must withstand continuous chewing pressure, both of which may lead to wear and shedding of the coating. This coating shedding may trigger an immune-inflammatory response, hinder bone integration, and affect the long-term stability of the implant. Therefore, although TNTs have great potential in advanced dental implants, overcoming the challenges associated with mechanical stability is crucial for their clinical application.

[0003] To enhance the mechanical stability of TNTs, a variety of methods have been proposed. One class of methods focuses on improving the interfacial adhesion between TNTs and the titanium substrate to enhance the coating's anti-delamination ability. For example, the addition of boric acid to the anodizing electrolyte has been found to effectively reduce the fluorine content, thereby enhancing the interfacial adhesion between the nanotube layer and the titanium substrate. Another class of methods uses techniques such as laser-induced surface modification to partially crystallize titanium dioxide, thereby significantly improving its mechanical properties. In addition, polymer-filled TNTs have also been shown to enhance their mechanical strength. However, during implant surgery, the implant will experience high torque during insertion and must withstand lateral friction. Existing reinforcement measures are still unable to effectively prevent TNTs from wear and fall off due to poor intrinsic adhesion and thin tube walls.

[0004] The present invention proposes a potential strategy to address the above-mentioned problems, namely, utilizing a hierarchical micropattern structure with interlocking protrusions and depressions to avoid direct contact between the nanotubes and the bone interface, thereby protecting the TNTs structure. These micropatterns can wrap unstable coatings in these micropatterns to avoid contact with friction. Specifically, micropatterning technology is assisted by picosecond laser etching technology to selectively remove photoresist in designated areas through laser-induced thermal effects, thereby creating microline patterns, and then directly anodizing these laser-etched microline pattern areas to form unique L-TNTs structures. However, no research in this regard has been reported so far. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is how to improve and effectively prevent the wear and falling off of TNTs caused by the problems of poor intrinsic adhesion and thin tube wall, and enhance its anti-stripping and wear resistance.

[0006] To achieve the above object, the present invention provides a novel anti-stripping L-TNTs array film prepared by laser assistance, comprising the following steps:

[0007] (1) spin coating a photoresist on a non-patterned area on the surface of the titanium-based material;

[0008] (2) etching the patterned area on the surface of the titanium-based material;

[0009] (3) anodizing the etched area;

[0010] (4) removing the photoresist to obtain an anti-stripping L-TNTs array film;

[0011] The surface structure of the novel anti-stripping L-TNTs array film is that TNTs are embedded in grooves formed by etching.

[0012] Preferably, the pattern is in the shape of a strip.

[0013] Preferably, the width of the stripe pattern is 50-600 μm.

[0014] Preferably, the width of the stripe pattern is 150-300 μm.

[0015] More preferably, the width of the stripe pattern is 300 μm.

[0016] Preferably, the width of the stripe pattern is 50-150 μm, 150-300 μm or 300-600 μm.

[0017] Preferably, the depth of the stripe pattern is 10-50 μm, and preferably, the depth of the stripe pattern is 20 μm.

[0018] Preferably, the etching in step (2) is physical etching or chemical etching.

[0019] Preferably, the chemical etching is laser etching.

[0020] Preferably, the laser is a picosecond ultraviolet laser.

[0021] Preferably, the power of the picosecond ultraviolet laser in step (2) is 1.5-45W, and preferably, the power of the picosecond ultraviolet laser is 15W.

[0022] Preferably, the electrolyte used for anodization in step (3) comprises deionized water, glycerol and ammonium fluoride, and the ratio of deionized water, glycerol and ammonium fluoride is 50:50:1.

[0023] Preferably, the voltage of the anodization in step (3) is 10-100V and the time is 0.5-1.5h.

[0024] Preferably, the voltage of the anodization in step (3) is 30 V and the time is 1 hour.

[0025] Preferably, the step of spin coating the photoresist in step (1) is to use a spin coater to spin coat 10 μL of the photoresist at a speed of 3000 rpm for 20 seconds to coat the L-TNTs sample.

[0026] Preferably, the method for preparing the novel anti-stripping TNTs array film further comprises a pre-treatment step: polishing, cleaning and drying the titanium-based material;

[0027] In a preferred embodiment of the present invention, the present invention provides an anti-stripping L-TNTs array film, which is prepared by the above method.

[0028] In another preferred embodiment of the present invention, the present invention provides a titanium-based dental implant, the surface of which is modified by an L-TNTs array film.

[0029] In another preferred embodiment of the present invention, the present invention provides the use of the L-TNTs array film of the present invention in improving the wear resistance and osteogenic differentiation ability of titanium implants.

[0030] The outstanding features and beneficial effects of the present invention are:

[0031] The novel anti-stripping L-TNTs array film of the present invention utilizes a hierarchical micropattern structure with interlocking protrusions and depressions to avoid direct contact between the nanotubes and the bone interface, thereby protecting the TNTs structure. The precise control of the micropattern structure size of the L-TNTs array film enhances the anti-stripping and wear resistance of the L-TNTs. In addition, L-TNTs can also be prepared on the curved surface of titanium implants. Although the TNTs structure is embedded in the depression structure of the titanium-based material, the L-TNTs still retain the ability of the nanotube structure to promote osteoblast growth and differentiation. These characteristics give L-TNTs significant potential to improve overall implant performance, promote the commercial application of TNTs, and lay a solid foundation for multifunctional implant research.

[0032] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Characterization of TNTs and L-TNTs. (A) OM and SEM images; (B) RR images; (C) Width measurements of gradient L-TNTs at 50 μm, 150 μm, 300 μm, and 600 μm line widths; (D) Surface roughness analysis; (E) Water contact angle measurements. Statistical significance is indicated by *(p<0.05) and **(p<0.01).

[0034] Figure 2 Stability evaluation of TNTs and L-TNTs: peel test. (A) Schematic diagram of the peel test; (B) OM and SEM images after the peel test; (C1-5) deformation-force curves; (D) statistical analysis of the maximum tensile force. Statistical significance is indicated by * (p < 0.05).

[0035] Figure 3 Stability evaluation of TNTs and L-TNTs: friction and wear tests under three lubrication conditions. (A) Schematic diagram of friction and wear test; (B) Optical microscopy (OM) images after friction and wear test.

[0036] Figure 4 Stability evaluation of TNTs and L-TNTs: friction and wear tests under three lubrication conditions. (A) Statistical analysis of wear width; (B) Statistical analysis of average friction coefficient. Statistical significance is marked with * (p < 0.05) and ** (p < 0.01).

[0037] Figure 5 Stability evaluation of TNTs and L-TNTs: friction and wear tests under three lubrication conditions. (A) RR images after friction and wear tests; (B) Friction coefficient curves.

[0038] Figure 6 In vitro viability assessment of TNTs and L-TNTs. (A) Inverted fluorescence microscopy (IFM) images of MC3T3-E1 cells on samples; (B) Statistical analysis of early adhesion; (C, D) Cell viability results. Statistical significance is marked as * (p<0.05), ** (p<0.01) and ns (p>0.01).

[0039] Figure 7 In vitro osteogenesis assessment of TNTs and L-TNTs. (A) Optical microscopy (OM) images of MC3T3-E1 cells on samples; (B, C) ALP activity statistical analysis; (D) mineralization analysis; (E1-5) RT-qPCR results related to osteogenic differentiation. Statistical significance is marked as * (p<0.05), ** (p<0.01) and ns (p>0.05).

[0040] Figure 8 Evaluation of the mechanical stability of TNTs and L-TNTs: in vitro testing. (A) Schematic diagram and image of the in vitro test on rabbit femur; (B) SEM images taken before and after insertion. Before insertion, the nanotube structure in both TNTs and L-TNTs remained intact. After insertion, the nanotube structure in TNTs peeled off, while the structure in L-TNTs remained intact.

[0041] Fig. 9 is the in vivo osteogenesis evaluation of TNTs and L-TNTs. (A) Surgical site in rabbit mandible (red arrow indicates implantation site); (B) Micro-CT image and histological results of HE staining and Masson staining one month after surgical implantation; (C) Statistical analysis of micro-CT evaluation. Statistical significance is indicated by * (p<0.05). DETAILED DESCRIPTION

[0042] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0043] Material

[0044] Titanium sheets and titanium wires used in this study were obtained from Fuxin Metal Co., Ltd., Baoji, Shanxi, China, and medical-grade TC4 titanium self-tapping screws (1 mm in diameter and 5 or 8 mm in length) were obtained from Jiangsu Baishe Co., Ltd., China, for the preparation of substrates for TNTs and L-TNTs. Photoresist materials were provided by Jiangsu Zhongxin Qiheng Co., Ltd., China, for the formation of micro-line patterns and selective anodization. All other reagents were purchased from Shanghai Aladdin Industrial Co., Ltd.

[0045] Example 1 Preparation and Characterization of TNTs and L-TNTs Samples

[0046] The titanium samples were cut into a size of 10100.2 mm and uniformly prepared by anodizing at a constant 30 V for 1 h in an electrolyte consisting of deionized water, glycerol and ammonium fluoride in a ratio of 50:50:1. The preparation of L-TNTs involves four steps: First, 10 μL of photoresist was spin-coated at 3000 rpm using a spin coater for 20 seconds to coat the L-TNTs sample. Subsequently, a 15 W picosecond UV laser (BGL-1064-15c, Xingyao, China) was used for etching, and the width was precisely controlled to 50 μm, 150 μm, 300 μm and 600 μm by galvanometer scanning. In the subsequent selective electrochemical anodization step, the sample was placed in the same electrolytic environment as the TNTs for anodization, and the area covered by the photoresist was isolated, thereby specifically modifying the laser etched area. Finally, a stripper was used to effectively remove the photoresist within a specified time. The obtained samples were micro-line patterned L-TNTs with sizes of 50 μm, 150 μm, 300 μm, and 600 μm, which were labeled as L50, L150, L300, and L600, respectively.

[0047] The morphology of TNTs and gradient L-TNTs samples was analyzed by optical microscopy (OM, A1, Zeiss, Germany) and scanning electron microscopy (SEM S-4800, Hitachi, Japan). The surface roughness and wettability of the samples were measured by roughness reconstruction (RR, XL, Phenom, Netherlands) and contact angle measurement (JGW-360A, Suntak, China), respectively.

[0048] The morphological characteristics of TNTs and gradient L-TNTs were observed by OM and SEM. Figure 1 A shows the successfully prepared TNTs with uniform nanotube structures. In contrast, the gradient L-TNTs show a complex hierarchical structure that seamlessly combines flat and nanotube structures and is clearly distinguished by distinct boundaries. It is worth noting that the gradient L-TNTs show a gradual increase in nanotube volume at different microline pattern widths (50μm, 150μm, 300μm, and 600μm), as shown in Figure 2. Figure 1 C. This stepwise change demonstrates the precise control achieved during the preparation process and contributes to its unique morphological properties.

[0049] Further use of RR( Figure 1 B) The chemical composition and surface roughness of TNTs and gradient L-TNTs were investigated. RR results showed that the surface roughness of gradient L-TNTs (50 μm) was slightly increased compared with that of conventional TNTs ( Figure 1D). In addition, the hydrophilicity of L-TNTs is significantly lower than that of TNTs ( Figure 1 E). Surface topography affects microstructure, physical properties, tribological characteristics, and surface roughness. The implementation of micro-line patterning technology significantly changes the topography, surface roughness, and hydrophilicity of conventional TNTs, improving the stability and functionality of the coating overall.

[0050] Example 2 Stability Test

[0051] To evaluate the mechanical stability of the coatings, peel tests were performed. According to the GBT228.1-2010 metal material tensile test standard, a universal testing machine (Model 3369, Instron, USA) was used to apply a standard tape pull at a speed of 1 mm / min at room temperature. After the test, all coatings showed damaged integrity. The morphology of the peeled area was analyzed using OM and SEM.

[0052] like Figure 2 A shows the controlled peeling of a standard tape firmly attached to TNTs / L-TNTs under increasing tensile stress during the test. The maximum force recorded during the test indicates the adhesion strength of the coating. Figure 2 B shows the morphology of the peeled area of ​​conventional TNTs and L-TNTs after tensile testing. In the case of TNTs, the peeled area shows a pitted structure due to the shedding of nanotubes, reflecting its poor adhesion to the substrate. In contrast, the nanotube structure of L-TNTs remains intact, especially in the 150μm and 300μm samples, indicating its superior adhesion. This enhanced adhesion is attributed to the micro-line pattern integrated in the TNTs, which enhances the mechanical interlocking between the TNTs and the titanium substrate. Although the tensile peeling test conducted in the test area posed a challenge to the adhesion between the TNTs and the titanium substrate, the overall structure of the L-TNTs remained intact with the titanium substrate, successfully maintaining the structural integrity of the TNTs in the modified L-TNTs.

[0053] During the tensile peel test, the peel force initially reaches a peak as delamination begins, and then the required peel force gradually increases. Figure 2 C1-5) and maximum tensile force measurement ( Figure 2 D) shows that the maximum tensile force of the L-TNTs group is significantly higher than that of the TNTs group, especially the 300μm L-TNTs (increased by 100%), further confirming the superior performance of L-TNTs. There is a statistically significant difference in the maximum tensile force requirements between L-TNTs and TNTs (p<0.05), which indicates the effectiveness of the micro-line pattern in stabilizing the coating.

[0054] The micro / nano hierarchical structure enhances the friction surface, while the discontinuous hierarchical structure affects the tensile fracture behavior. This strong adhesion can be achieved through stress relaxation and crack deflection at the Ti / TNTs interface, thereby increasing the shear force required for peeling, regulating dislocation motion, and inhibiting crack propagation through a multilayer structure with short-period repeated interfaces.

[0055] Example 3 Friction and wear behavior

[0056] The friction and wear behavior of the samples were evaluated using an electrochemical reciprocating friction and wear tester (MSR-2T, Kaihua, China) under ball-plane contact conditions. The test conditions were 50 g load, 10 min duration, 500 times / min speed, and a reciprocating length of 5 mm.

[0057] Different lubricating media will lead to different friction coefficients and wear volumes. Three lubricating media were selected in this paper: dry conditions, Hanks balanced salt solution (HBSS) simulating body fluids, and artificial saliva (AS) simulating oral environment.

[0058] The wear resistance of L-TNTs and conventional TNTs on titanium substrates was evaluated by the average friction coefficient and wear width. Figure 3 A. Both coatings showed the highest wear width and average friction coefficient under dry conditions, while the lowest values ​​were recorded under AS conditions. In the HBSS and AS simulated oral environments, the fluid promoted the removal of wear particles, thereby reducing abrasive wear, smoothing the friction coefficient curve, and reducing the average friction coefficient and wear width.

[0059] OM Image ( Figure 3 B)RR( Figure 5 A) and friction coefficient curve ( Figure 5 B) shows that under three different lubrication conditions, conventional TNTs consistently show deeper wear tracks and wider grooves, indicating a higher level of wear. In contrast, L-TNTs, especially the 300 μm variant, facilitate the accumulation of wear particles in the contact zone, thereby enhancing the resistance to abrasive wear and resulting in a narrower and shallower wear pattern ( Figure 4 A) and a lower average friction coefficient ( Figure 4 B). Therefore, micro-line pattern modification significantly improves the wear resistance of TNTs, which may be attributed to the reduction of the generation of reinforcing abrasive debris in third-body wear and surface wear. L-TNTs, especially the 300 μm variant, enhance the wear resistance and mechanical stability of TNTs, indicating better long-term effectiveness in applications involving wear and abrasion resistance.

[0060] Example 4 In vitro osteogenesis experiment

[0061] In vitro osteogenesis experiments were performed using mouse osteogenic precursor cell line MC3T3-E1 (ATCC, China). Cells were cultured in α-MEM medium containing 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin / streptomycin (PS, Gibco, USA) and maintained at 37°C in a 5% CO2 atmosphere. Passage was performed when the cell density reached 80-90%. Before any in vitro experiments, all samples were sterilized by soaking in 75% ethanol solution for 30 minutes and then air-dried.

[0062] 1. Cell morphology, early adhesion and viability test

[0063] The cell morphology was observed using an inverted fluorescence microscope (IFM, OLYMPUS IX71, Japan). MC3T3-E1 cells were plated at 8×10 3 The cells were seeded at a density of 10 cells / mL in 24-well plates and cultured for 3 days. Subsequently, the samples were washed and fixed in 4% paraformaldehyde, and the cells were stained with fluorescein isothiocyanate (FITC)-labeled phalloidin and 4′,6-diamidino-2-phenylindole (DAPI) to observe the morphology.

[0064] To evaluate cell adhesion, fluorescent staining was used. MC3T3-E1 cells were plated at 2×10 4 Cells were seeded at a density of 10 cells / mL in 24-well plates and after incubation on the samples for 3 h, the cells were washed, fixed, and stained with DAPI to visualize the nuclei. They were observed by IFM and further analyzed using Image J software.

[0065] The viability of MC3T3-E1 cells on each sample was evaluated using the MTT test. The cells were seeded in a 24-well plate at a density of 2×104 cells / mL, and after culturing for 4 and 7 days, the samples were washed with PBS. Subsequently, 300 μL of incomplete culture medium and 30 μL of MTT solution were added to each well and incubated at 37°C for 4 hours. Afterwards, 1 mL of DMSO was added to dissolve the formazan crystals formed. The optical density of the solution was measured at a wavelength of 490 nm using a microplate reader (Bio-Rad 680, USA).

[0066] Fluorescence microscopy (FM) results showed that L-TNTs significantly enhanced cell extension and cell-to-cell connections compared to conventional TNTs. In TNTs, cells mainly exhibited a spindle shape and formed point-to-point connections with neighboring cells. In contrast, in L-TNTs, especially the 300 μm variant, cells exhibited an extended polygonal morphology and established point-to-face connections ( Figure 6 A) This cell-cell junction region promotes cell extension, indicating that L-TNTs are more efficient in promoting cell extension and cell-to-cell communication compared to TNTs.

[0067] FM and statistical analysis confirmed that L-TNTs significantly enhanced the adhesion of MC3T3-E1 cells at the early stage ( Figure 6 A and B). In addition, after 4 and 7 days of culture, the cell viability in the L-TNTs (50 μm and 300 μm) groups was significantly increased (p < 0.05) ( Figure 6 C and D). These results indicate that L-TNTs promoted early cell adhesion by at least 20% and enhanced cell viability in the 50μm and 300μm groups, demonstrating superior biocompatibility compared to TNTs. The pore size of 300μm is more suitable for bone tissue engineering. The micro-nano composite structure enhances the biological behavior of osteoblasts. The micro- and nanostructures effectively affect cell behavior by simulating the extracellular matrix (ECM). In addition, the micropattern structure can regulate the stress state of macrophages, thereby affecting their phenotype and function, and ultimately regulating the body's immune response to biomaterials. The microline pattern and nanotube structure of L-TNTs promoted the adhesion, viability, and expansion behavior of MC3T3-E1 cells.

[0068] 2. In vitro osteogenic differentiation assay

[0069] In vitro osteogenic differentiation experiments included alkaline phosphatase (ALP) activity test, mineralization experiment and expression analysis of osteogenesis-related genes.

[0070] To evaluate the differentiation potential of MC3T3-E1 cells, ALP activity was quantified. 4 Cells were seeded at a density of 10 cells / mL in 24-well plates. After 4 and 7 days of culture, cells were lysed using 1% Triton X-100, and ALP activity was determined using an ALP assay kit (Nanjing Jiancheng Bioengineering Institute, China), and total protein content was determined using a BCA protein assay kit (Biyuntian, China). The total intracellular protein content obtained by BCA protein assay was used to normalize the ALP results.

[0071] For mineralization experiments, MC3T3-E1 cells were cultured at 2 × 10 4 The density of cells / mL was inoculated on different samples in 24-well plates and cultured in α-MEM medium. After 14 days of osteogenic induction, the samples were fixed and stained with Alizarin Red S for 60 minutes. Five fields of view were randomly selected using a stereomicroscope to observe the mineralized nodules. Then, the mineralized nodules were dissolved in 1mL of 10% cetylpyridinium chloride solution, and the absorbance of the resulting solution was measured at a wavelength of 540nm using a microplate reader (Bio-Rad 680, USA) for quantitative analysis.

[0072] The expression of genes related to osteogenesis was evaluated by reverse transcription-polymerase chain reaction (RT-qPCR). 4 MC3T3-E1 cells were inoculated on sterilized samples at a density of 10 cells / mL. After 7 days of culture, total RNA was extracted using RNAsimple Total RNA Kit (Tiangen, China) and quantified by NanoDrop2000 spectrophotometer. Then, mRNA was reverse transcribed into cDNA using PrimeScript RT Reagent Kit (TAKARA, Japan). SYBR Premix Ex TM The expression levels of osteogenic genes such as alkaline phosphatase (ALP), type I collagen (COL-1), osteocalcin (OCN), osteoprotegerin (OPG), and Runx-related transcription factor 2 (RUNX-2) were measured using a Taq II kit (TAKARA, Japan), and GAPDH was used as an internal reference gene.

[0073] The early osteogenic differentiation stage of MC3T3-E1 cells was assessed by measuring the ALP activity, a major osteogenic differentiation marker. Notably, in L-TNTs (300 μm and 600 μm), ALP activity was significantly enhanced after 4 and 7 days of culture, as shown in Figure 2. Figure 7 B and C. In addition, the relative gene expression of ALP and COL-1 mRNA in L-TNTs (300 μm) showed significant improvement (increase of 10%) after 7 days of culture, compared with that in conventional TNTs, as shown in Figure 2. Figure 7 E1-5. Accordingly, after 14 days of culture, the mineralization level of L-TNTs (300 μm) was superior to that of TNTs ( Figure 7 A and D). Micro / nanotexturing of titanium-based surfaces enhances cytocompatibility and osteogenic activity. L-TNTs with microline patterns and nanotube structures significantly increased the ALP activity and mineralization level of MC3T3-E1 cells.

[0074] Example 5 Ex vivo screw implantation and removal test

[0075] Ex vivo tests were performed to analyze the mechanical properties of the coatings in a simulated clinical setting. Holes were drilled using a 0.8 mm spherical drill bit, and TNTs and L-TNTs self-tapping screws were implanted into the rabbit tibia and screwed in using a fixed torque screwdriver (Aigu, Guangdong, China) until no further advancement was possible. The screw implants were then removed, washed, dried, and sintered to eliminate organic components. Subsequently, the samples were observed using SEM.

[0076] During surgical implantation or under functional load, dental implants may be subjected to shear forces, which may lead to cracking or loss of TNTs. In order to evaluate the biomechanical stability of TNTs and L-TNTs in a simulated surgical implantation environment, in vitro tests were performed ( Figure 8 A). Figure 8 As shown in B, SEM comparative analysis of the implant surface before and after insertion revealed that in TNTs, the integrity of the nanotube structure was compromised, likely due to peeling caused by shear forces during insertion. This could lead to debris-induced foreign body reaction (FBR) and hinder bone integration. In contrast, L-TNTs maintained the integrity of the nanotube structure and demonstrated better structural stability. This suggests that L-TNTs are tougher and can protect the TNT structure from falling off, providing a potential improvement over TNTs in terms of mechanical stability.

[0077] Example 6 In vivo osteogenesis assessment

[0078] 1. Rabbit mandibular implant model

[0079] After anesthesia by intravenous injection of 3% sodium pentobarbital (1 mL / kg), 4-week-old male New Zealand white rabbits weighing 2.5 kg were randomly divided into two groups: TNTs and L-TNTs screw implants (1 mm in diameter and 5 mm in length). The surgical area was disinfected and local infiltration anesthesia was performed with 3% lidocaine hydrochloride. An incision was made along the skin, subcutaneous tissue, muscle, and periosteum in the mandible to expose the bone. An implant hole with a diameter of 0.8 mm and a depth of 4 mm was prepared, and the implant was inserted using a torque-controlled screwdriver to simulate the clinical surgical procedure. The muscle tissue and skin were then sutured to complete the mandibular implant model.

[0080] One month later, the samples were collected and fixed, and the precision of the surgery was evaluated by X-ray, micro-CT, and histological assessment to avoid the tooth root and evaluate the stability of the implanted screw. All animal experimental protocols were reviewed and approved by the Animal Ethics Committee of Wenzhou Research Institute (No. WIUCAS23032203), affiliated to the University of Chinese Academy of Sciences, and followed the guidelines of the Animal Care and Ethics Committee of China.

[0081] This study selected the rabbit mandibular implant repair model based on its similarity to the clinical implant insertion scenario ( Fig. 9 A). X-ray images from top and side views show the screw implant between the anterior and posterior teeth in the rabbit mandible, indicating the ideal position of the implant.

[0082] 2. Micro-CT detection

[0083] Micro-CT (Skyscan 1176, Bruker, Germany) was used to scan the mandibular implant sites and evaluate the osteogenesis around the implants in rabbits. Key parameters such as bone mineral density (BMD), new bone volume (BV / TV), trabecular thickness (Tb.Th) and trabecular separation (Tb.Sp) were quantitatively analyzed.

[0084] Analysis of the newly formed bone by Micro-CT images showed that L-TNTs and TNTs screw implants showed different degrees of high-density imaging in the screw head to thread area, accompanied by significant bone growth, such as Fig. 9 B. In particular, more new bone formation was observed around L-TNTs compared with TNTs. This observation was confirmed by the bone mass measurement software CTan and CTVoxel. Quantitative analysis of osteogenic indices, including bone mineral density (BMD), bone volume / total volume ratio (BV / TV%), trabecular thickness (Tb.Th), and trabecular spacing (Tb.Sp), was performed as shown in Figure 2. Fig. 9 As shown in C, L-TNTs significantly increased BMD, Tb.Th, and Tb.Sp, indicating an improvement in bone quality, while a slight increase in BV / TV showed no significant difference, indicating minimal changes in bone volume ratio, highlighting the superior osteoinductive capacity of L-TNTs relative to TNTs.

[0085] 3. In Vivo Osteogenesis Assessment

[0086] Mandibular bone samples in the experiment were decalcified using 12% ethylenediaminetetraacetic acid (EDTA, pH 7.4) for 60 days. After careful removal of the implants, the samples were dehydrated in a series of graded ethanol solutions and then embedded in paraffin. Subsequently, the samples were stained using hematoxylin-eosin (HE) and Masson's trichrome staining.

[0087] 4. Statistical Analysis

[0088] All experiments were repeated at least three times, and quantitative data are presented as mean ± standard deviation (SD). Data were analyzed using one-way analysis of variance (ANOVA) and statistically analyzed by Tukey's multiple comparison test at a 95% confidence level using GraphPad Prism (version 7.0, San Diego, USA).

[0089] HE and Masson staining were used to verify the new bone formation around the implants. Fig. 9As shown in B, HE staining showed an increase in osteoid tissue around L-TNTs compared with TNTs. Masson staining showed that the bone interface around L-TNTs was significantly thickened, and the newly formed bone tissue was blue, indicating that new bone formation was enhanced. Combined with micro-CT and histological analysis, L-TNTs enhanced the formation of new bone in the rabbit implant repair model, showing a superior osteogenesis effect than TNTs.

[0090] Compared with traditional TNTs, L-TNTs can precisely control the microstructure size and form a hierarchical structure by introducing microline pattern separation, demonstrating enhanced mechanical strength and functionality. This innovative approach ensures effective protection and stability of TNTs under mechanical stress, which is critical for potential applications in dental implants and other high-demand environments. These properties give L-TNTs significant potential to improve implant performance while maintaining their efficacy in promoting bone integration both in vitro and in vivo. The L-TNTs developed in this study provide a promising new platform for the development of multifunctional implants in dental implantology and lay a solid foundation for the widespread application of TNTs.

[0091] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A titanium-based dental implant, wherein the surface of the dental implant is modified by an anti-stripping L-TNTs array film.

2. A method for preparing a novel laser-assisted anti-stripping L-TNTs array film, comprising the following steps: (1) spin coating a photoresist on a non-patterned area on the surface of the titanium-based material; (2) etching the patterned area on the surface of the titanium-based material; (3) anodizing the etched area; (4) removing the photoresist to obtain an anti-stripping L-TNTs array film; The surface structure of the novel anti-stripping L-TNTs array film is that TNTs are embedded in grooves formed by etching.

3. The method for preparing the novel anti-stripping L-TNTs array film according to claim 2, characterized in that: The pattern is in the shape of a strip.

4. The method for preparing the novel anti-stripping L-TNTs array film according to claim 3, characterized in that: The width of the stripe pattern is 50-600 μm, preferably, the width of the stripe pattern is 150-300 μm, more preferably, the width of the stripe pattern is 300 μm; Optionally, the depth of the stripe pattern is 10-50 μm, preferably, the depth of the stripe pattern is 20 μm.

5. The method for preparing the novel anti-stripping L-TNTs array film according to claim 2, characterized in that: The etching in step (2) is performed by physical etching or chemical etching, the chemical etching is preferably laser etching, and the laser is preferably picosecond ultraviolet laser; Optionally, the power of the picosecond ultraviolet laser in step (2) is 1.5-45W, preferably, the power of the picosecond ultraviolet laser is 15W.

6. The method for preparing the novel anti-stripping L-TNTs array film according to claim 2, characterized in that: The electrolyte used for anodization in step (3) includes deionized water, glycerol and ammonium fluoride, and the ratio of deionized water, glycerol and ammonium fluoride is 50:50:

1. Optionally, the voltage of anodization in step (3) is 10-100V, and the time is 0.5-1.5h.

7. The method for preparing the novel anti-stripping L-TNTs array film according to claim 2, characterized in that: The step of spin coating the photoresist in step (1) is to use a spin coater to spin coat 5-15 μL of the photoresist at a speed of 2000-4000 rpm for 10-50 seconds to coat the L-TNTs sample.

8. The method for preparing the novel anti-stripping L-TNTs array film according to claim 2, characterized in that: The method for preparing the L-TNTs array film also includes a pre-treatment step: polishing, cleaning and drying the titanium-based material.

9. The anti-stripping L-TNTs array film obtained by the preparation method of the novel anti-stripping L-TNTs array film according to claims 2-8.

10. Use of the novel anti-stripping L-TNTs array film prepared by the preparation method described in claims 2-8 or the anti-stripping L-TNTs array film described in claim 9 in improving the wear resistance and osteogenic differentiation ability of titanium implants.